The impact of social media marketing on brand equity: A systematic review - Ra’d Almestarihi, Jassim Ahmad Al-Gasawneh, Sameer Al-jabali, Malik Khlaif Gharaibeh, Enaizan, Odai Nawras, M. Nusairat, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
social media has impacted all types of business and marketing in terms of promoting brands and enhanced their equity. This study aims to identify, evaluate, summarize and synthesize findings of previous studies that tested the impact of social media marketing on building brand equity and to classify the included studies according to brand equity components, platforms, social media dimensions, and type of industry. The study selection process is outlined according to the PRISMA statement. An online search carried out of 11 databases using combinations of all possible keywords and phrases. Clear, specific, and predefined eligibility criteria were applied to identify studies that related to the topic. Search results were transferred into Endnotes software to remove duplication, article and abstract were scanned of records that are related to the topic. a total of 26 papers that meet inclusion criteria were included, most studies have reported an influence of social media on brand awareness, brand associations, perceived quality, and brand loyalty. Further, this study reported that the Facebook platform was dominant among studies, several industries were tested and most studies have reported the five dimensions of social media. To sum up, social media marketing positively impacted CBBE dimensions namely brand awareness, perceived quality, association, and loyalty.